A nano-sized container for specific encapsulation of isolated water molecules. Issue 98 (18th November 2016) - Lavendomme, Roy; Marcélis, Lionel; Wouters, Johan; Luhmer, Michel; Jabin, Ivan
Abstract : This calix[4]arene-based molecular box is able to encapsulate specifically two isolated water molecules in both non-protic and protic solvents. Abstract : A calix[4]arene-based molecular box was synthesized. Its properties were characterized through XRD and extensive NMR studies. This receptor is able to encapsulate specifically two isolated water molecules in both non-protic and protic solvents. This is a consequence of high size, geometric and electronic complementarity between the host and the water molecules.